2013
DOI: 10.1002/jat.2936
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological findings on Carassius auratus hepatopancreas upon exposure to acrylamide: correlation with genotoxicity and metabolic alterations

Abstract: Acrylamide is an amide used in several industrial applications making it easily discharged to aquatic ecosystems. The toxicity of acrylamide to aquatic organisms is scarcely known, although previous studies with murine models provided evidence for deleterious effects. To assess the effects of acrylamide to freshwater fish, goldfish (Carassius auratus L.) were exposed to several concentrations of waterborne acrylamide and analysed for genotoxic damage, alterations to detoxifying enzymes and histopathology. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 81 publications
(71 reference statements)
0
14
1
Order By: Relevance
“…Acrylamide toxicity study conducted in two species of aquatic macroinvertebrates and three species of fish demonstrated that acrylamide was moderately toxic aquatic organisms [14]. There was also histopathological changes and correlation with genotoxicity and metabolic alterations when Carassius auratus hepatopancreas (goldfish) was exposed to acrylamide [15].…”
Section: Introductionmentioning
confidence: 99%
“…Acrylamide toxicity study conducted in two species of aquatic macroinvertebrates and three species of fish demonstrated that acrylamide was moderately toxic aquatic organisms [14]. There was also histopathological changes and correlation with genotoxicity and metabolic alterations when Carassius auratus hepatopancreas (goldfish) was exposed to acrylamide [15].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple adverse effects of acrylamide have been demonstrated, including reproductive toxicity, carcinogenicity and neurotoxicity (Hasegawa et al, 2004;Walters et al, 2014;Xu et al, 2014). Acrylamide can induce litter size, DNA strand breaks and lethal mutations (Larguinho et al, 2014;Tyl et al, 2000;Wang et al, 2010). Previous studies have shown the carcinogenic effects of acrylamide in experimental animals (Ao & Cao, 2012;Bull et al, 1984;Friedman et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Toxicity studies have revealed moderate to low effects of acrylamide monomers to aquatic wildlife, especially to fish and crustaceans [55][56][57]. Environmentally relevant chronic, sublethal doses of anionic polymer products to juvenile rainbow trout resulted in either no damage or very low levels of damage to gill tissue.…”
Section: Toxic Effectsmentioning
confidence: 99%
“…Acrylamide has been shown to cause severe pancreatic tissue lesions in goldfish, which added a most probable effect as a genotoxicant and probable mutagenic agent in fish [57]. Another study with goldfish demonstrated that acrylamide is genotoxic in blood erythrocytes; this leads to cancer in individuals, and also disrupts homeostasis of organisms and introduces genetic diversity [60].…”
Section: Toxic Effectsmentioning
confidence: 99%
See 1 more Smart Citation